Association of vascular endothelial growth factor a gene (VEGFA) polymorphisms, rs699947 and rs1570360, with diabetic retinopathy and altered VEGF secretion in the Pakistani patients with type 2 diabetes mellitus: a case-control study - Shazia Qayyum; Muhammad Afzal; Abdul Khaliq Naveed; Butt, Imran Azam; Madiha Sajjad; Moiz Azam (Journal of the Pakistan Medical Association, 2023)
Objective: To investigate the association of vascular endothelial growth factor A gene polymorphisms 2578C/A (rs699947) and 1154G/A (rs1570360) with type 2 diabetes mellitus, diabetic retinopathy and serum vascular endothelial growth factor levels in Pakistani patients. Method: The case-control study was conducted from Jan 2017 to Dec 2018 after approval from the ethics review board of Riphah International University, Islamabad, Pakistan, and comprised type 2 diabetes mellitus patients of either gender with diabetic retinopathy in group A, and without diabetic retinopathy in group B. Non-diabetic healthy individuals were enrolled in control group C. Genotyping was done by amplification refractory mutation system-polymerase chain reaction and serum vascular endothelial growth factor levels were measured using enzyme-linked immunosorbent assay. Data was analysed using SPSS 22. Results: Of the 450 subjects, 150(33.3%) were in each of the 3 groups. The mean age in group A was 58.16±9.42, in group B 56.25±8.5 years and in group C it was 55.90±10.90. The proportion of Punjabi ethnicity was significantly high in group B compared to other groups (p<0.05). There was no significant association of rs699947 and rs1570360 genotypic and allelic frequencies in group B compared to group A. Further, rs699947 AA genotype was significantly associated with proliferative diabetic retinopathy compared to group A (p<0.05). Minor allele A showed significant association in groups A and B compared to group C (p<0.05). Significantly raised serum vascular endothelial growth factor levels were found in group B compared to group A (p<0.05), and were associated with rs699947 and rs1570360 heterozygosity in group A (p<0.05). Also, rs699947 genotype showed significant association with groups A and B in Punjabi and Pathan ethnicities (p<0.05) and with Kashmiri ethnicity in group B (p<0.05). Conclusion: There was a strong association of vascular endothelial growth factor 2578C/A (rs699947) gene polymorphism with proliferative diabetic retinopathy in type 2 diabetic Pakistani patients, suggesting its role in the pathogenesis of this condition. Key Words: Diabetic retinopathy, Polymorphisms, Type 2 diabetes mellitus, Vascular endothelial growth factor A gene.